Health‐related quality of life of patients with multiple myeloma: A real‐world study in China. (2nd September 2020) - Li, Xiaozhe; Liu, Junru; Chen, Meilan; Gu, Jingli; Huang, Beihui; Zheng, Dong; Li, Juan
Abstract: Purpose: This study aimed to assess the health‐related quality of life (HRQOL) of Chinese patients with different stages of multiple myeloma (MM) who received various treatments and identify the factors associated with a lower quality of life in China. Methods: A cross‐sectional, anonymous questionnaire was distributed to adults with MM. The measures of quality of life included the European Organization for Research and Treatment of Cancer (EORTC) quality of life questionnaire (QLQ)‐C30, QLQ‐myeloma‐specific module 20 (MY20), and EuroQoL EQ‐5D. The data, including patient factors, difficulties experienced during the diagnosis and treatment processes, psychosocial factors and disease‐ or treatment‐related effects, were collected. Results: Four hundred and thirty patients with MM were recruited from all 27 provinces of China, and their average age was 55.7 years. Many variables were significantly associated with the HRQOL of the patients with MM. In the multivariate analyses, performance status, psychosocial factors, disease phase, and an early diagnosis were significantly associated with the HRQOL. In the subgroup analysis, the HRQOL of the patients who underwent autologous stem cell transplantation (ASCT) was significantly higher than that of the non‐ASCT patients. Treatment‐related toxicities had a significant impact on the quality of life of the patients with MM, and 91.5% of the patients intended to stop the maintenance treatment. Conclusions: The quality of life of patients with MM in China is affected by patient factors, difficulties experienced during the diagnosis and treatment processes, psychosocial factors, and disease‐ or treatment‐related effects. Efforts should be exerted to improve the overall quality of life of these patients in China. Abstract : This study aimed to assess the health‐related quality of life (HRQOL) among Chinese patients with different stages of multiple myeloma (MM) who received various treatments and to determine which factors are associated with a lower quality of life in this population in China.